Implementasi Manajemen Mutu Dalam Meningkatkan Kompetensi Profesional Guru di Madrasah Aliyah Biharul Ulum Ma'arif - Herlinda Herlinda (Education Management: Jurnal Manajemen Pendidikan Islam (Edium), 2023)
Abstract : Quality management is a way to continuously and irrationally improve institutional performance by utilizing several elements such as human resources, capital and facilities. Teacher professional competence still needs a lot of attention until now. Because teachers are the main capital to create a generation of quality and character-educated nations. This research is a qualitative research by means of a case study. Data collection was carried out using the method of observation, interviews and documentation. This study aims to identify and find out quality management problems in improving teacher professionalism at MA Biharul Ulum Ma'arif. To obtain data, the subjects of this study were the head of the madrasa, wakamad and teachers at MA Biharul Ulum Ma'arif. In addition, this study tested the validity of the data using the triangulation technique. The results of this study indicate that (1) Quality management planning in increasing the professionalism of MA Biharul Ulum Ma'arif teachers has not been maximized, there are still plans that have not been implemented. This is still limited by supporting factors such as financing and supporting facilities. (2) The implementation of quality management in improving the professional competence of MA Biharul Ulum Ma'arif teachers is not in accordance with the provisions and work relations still need to be improved (3) The implementation of quality management in improving the professional competence of MA Biharul Ulum Ma'arif teachers has not run optimally, there are several deficiencies and inhibiting factors that need to be followed up. (4) Quality management control in improving the professional competence of MA Biharul Ulum Ma'arif teachers, especially in the evaluation program, still needs to be maximized.